2013
DOI: 10.1111/bjet.12007
|View full text |Cite
|
Sign up to set email alerts
|

The Internet in face‐to‐face higher education: Can interactive learning improve academic achievement?

Abstract: Recent research on e-learning shows that blended learning is more effective than faceto-face learning. However, a clear empirical response has not been given to the cause of such improvement. Using a data set of 9044 students at two Catalan universities and a quasi-experimental approach, two possible hypotheses identified in previous research are studied. The results show that the principal cause of the improvement is not, in itself, the increase in time spent online for educational purposes. Rather, increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 23 publications
2
58
1
2
Order By: Relevance
“…This result was consistent with previous research which showed how interaction skills were more important than information skills for taking advantage of and being successful in online courses (Bernard et al 2009;Castaño-Muñoz et al 2014). …”
Section: Influence Of Digital Competence On Mooc Participationsupporting
confidence: 93%
“…This result was consistent with previous research which showed how interaction skills were more important than information skills for taking advantage of and being successful in online courses (Bernard et al 2009;Castaño-Muñoz et al 2014). …”
Section: Influence Of Digital Competence On Mooc Participationsupporting
confidence: 93%
“…There is evidence suggesting that the time spent studying online does not necessarily imply better results (Castaño-Muñoz, Duart, & Sancho-Vinuesa, 2014). Positive effects can be found in the levels of learning and in the results obtained by students (Leung & Lee, 2012;López-Pérez, Pérez-López, Rodríguez-Ariza, & Argente-Linares, 2013;Markovíc & Jovanovíc, 2012;Mohd & Maat, 2013).…”
Section: Technology and Academic Performancementioning
confidence: 99%
“…Setting aside enough time for learning is important for cognitive as well as for emotional factors in learning; it leaves room to apply cognitive and meta-cognitive strategies, maintains motivation, and prevents unpleasant experiences such as feelings of anxiety, tension, or time pressure (Macher et al 2012;Pintrich and de Groot 1990;Zimmerman 1990). However, even though setting aside enough time for learning is important for achievement, the actual use of time is more crucial (Castaño-Muñoz et al 2014). Students in group 1 integrated different representations of content in their learning processes, podcasts, the additional mainly text-based learning material, and at least some lectures.…”
Section: Latent Class Analysis Identified Three Groups (Research Quesmentioning
confidence: 99%